PENGARUH FASILITAS KANTOR DAN DISIPLIN KERJA TERHADAP KINERJA PEGAWAI - MULIATI, MULIATI; Murbayani, Murbayani (Patria Artha University, 2023)
This study aims to analyze the effect of office facilities and work disciplineindividually or jointly on employee performance at the Balocci District Office, Pangkep Regency. The research population is employees at the Balocci District Office, Pangkep Regency, which was recorded in 2021 as many as 23 employees. The data analysis technique used in this study consisted of validity and reliability tests, descriptive analysis, classical assumption tests and hypothesis testing. The results showed that:1) office facilities had a positive effect of 0.498 and significant on employee performance at theBalocci District Office, Pangkep Regency; 2) work discipline has apositive effect of 0.452 and is significant on employee performance at the Balocci District Office, Pangkep Regency; 3) Office facilities and work discipline have a simultaneous positive and significant effect on employee performance at the Balocci District Office, Pangkep Regency with a contribution of 36.6%.